MICROPLASTIC CHARACTERISTIC FOUND IN GASTROINTESTINAL TRACT OF PELAGIC AND DEMERSAL FISHES IN TUBAN, EAST JAVA - Hidayati, Dewi; F, Fauziah; A, Aunurohim; Ashuri, Nova Maulidina; Setiawan, Edwin; Mulyadi, Yeyes; Syahroni, Nur; Joesidawati, Marita Ika; S, Suwarsih (Journal of Marine-Earth Science and Technology, 2023)
Regular monitoring of microplastics contamination in marine biota have been concerned in the world, since its tiny size can be swallowed direct or indirectly and lead health problems. Tuban waters is the one of Indonesia's coastal and marine fisheries areas with high risk of microplastic pollution due to their highly anthropogenic activities. We investigated the microplastic in the digestive tracts of pelagic and demersal fishes in Tuban sea waters. Microplastic in fish sample guts were observed under microscope and the type of polymer were examined using FT-IR. This study reveals that number of microplastic in digestive tract of pelagic fishes were higher than demersal fishes. The dominant form was fiber (62%) with black color and dominant size ranging from 100-500 um (72%). The types of polymers found were polyethylene and polyamide.